The Effect of Industrial Type, Environmental Performance and Leverage on Carbon Emission Disclosure: Evidence from Indonesian LQ45 Companies - Meiryani, Meiryani; Huang, Shi-Ming; Warganegara, Dezie Leonarda; Ariefianto, Moch Doddy; Teresa, Vaeren; Oktavianie, Helda (International Journal of Energy Economics and Policy, 2023)
This study aims to examine and look for empirical evidence related to the determinants that influence the carbon emissions disclosure. The factors tested in this study include industrial type, environmental performance, leverage, and profitability. This research method uses a quantitative approach. The source of data in this study uses secondary data, namely data from sustainability reports and annual reports. The population used is all LQ45 index companies listed on the Indonesia Stock Exchange in 2016 – 2020 and this study uses purposive sampling technique. This study uses tests such as descriptive statistical analysis, classical assumption test, hypothesis testing and multiple linear regression analysis. The results of this study indicate that the industrial type and CEO tenure have no effect on carbon emission disclosures, while leverage, profitability, environmental performance, CEO gender and technology for disclosure have a negative effect on carbon emission disclosures.